Early identification of autism spectrum disorder in preschoolers by static and dynamic amplitude of low-frequency fluctuations features - Yu, Kanghui; Xu, Shoujun; Fu, Shishun; Hua, Kelei; Yin, Yi; Lei, Qiang; Liu, Jinwu; Wu, Yunfan; Jiang, Guihua (Frontiers in Human Neuroscience, 2025)
ObjectivesEarly identification and timely intervention is critical for young children with autism spectrum disorder (ASD). The current study aims to explore potential disparities in static and dynamic intrinsic brain function in preschoolers with ASD, and uncover underlying neural underpinnings that can be used for facilitating the identification of ASD.Materials and methodsStatic and dynamic amplitude of low-frequency fluctuations (ALFF) of 73 ASD preschoolers and 43 age-matched typically developing individuals (TDs) were extracted and compared to identify differences in intrinsic brain local connectivity associated with ASD. The dynamic ALFF (dALFF) utilized a sliding window technique that integrates static ALFF (sALFF) to gauge the variance of local brain activity over time. A receiver operating characteristic (ROC) analysis was conducted to evaluate the potential diagnostic capability of the sALFF and dALFF metrics in identifying ASD.ResultsCompared with TDs, ASD preschoolers exhibited lower levels of sALFF in the left middle temporal gyrus, medial orbitofrontal cortex, precuneus and reduced dALFF values in the left inferior orbitofrontal cortex, middle temporal gyrus. ROC analysis indicated that sALFF and dALFF could distinguish preschoolers with ASD from TDs with the areas under the curve (AUC) of 0.848 and 0.744 (p < 0.001), and their combination showed an increased accuracy with the AUC of 0.866 (p < 0.001). Nevertheless, there were no linear correlation between the ALFF values in children with ASD and clinical scales.ConclusionThe findings suggest an association of regional left brain dysfunction with ASD in preschoolers. The values of sALFF and dALFF, particularly in the middle temporal gyrus, could act as possible indicators for the early detection of ASD.